Health professionals and scientists’ views on genome-wide NIPT in the French public health system: critical analysis of the ethical issues raised by prenatal genomics - Perrot, A; Horn, R (Public Library of Science, 2022)
In France, since January 2020, laboratories have started to make available genome-wide Non-Invasive Prenatal Testing (GW-NIPT) beyond the three common trisomies (T21, T13 and T18) at the same cost as standard NIPT. With the possible margins for interpretation of the legal framework and in the absence of clear and updated guidelines, health professionals are left with questions about which type of screening offer may be clinically responsible, morally appropriate, and, at the same time, respectful of women’s values and ability to make autonomous choices. The aim of this study is to provide an analysis and understanding of the challenging dimensions of clinical practices in the context of evolving scientific knowledge and techniques in prenatal genomics. In this article, we develop a critical analysis of the arguments and concerns that emerge around the offer of expanded NIPT and are discussed by health professionals and scientists. To achieve this, we conducted qualitative semi-structured interviews with 17 health professionals and scientists from September 2021 to February 2022 and a comprehensive literature review (regulatory, scientific, medical, institutional sources). The results of our empirical research highlight the importance of addressing ethical issues related to the differing quality of counselling, the complexity of achieving informed consent, and the avoidance of harm to pregnant women in the feedback of findings beyond T21, T18 and T13. If there is an increase in the provision of GW-NIPT within the French public health system, it will be essential to promote medical practices that respect reproductive choices of women, support their autonomous decision and their understanding of the limitations and uncertainties associated with GW screening. Further research is required to provide an insight into women’s perceptions in order to refine our analysis from the patients’ perspective.